THE EFFECTIVENESS OF KAFFIR LIME PEEL EXTRACT (Citrus hystrix) ON PLASMA MALONDIALDEHYDE LEVEL IN DEMENTIA MICE - Muhammad Ilham; Endang Mahati; Muflihatul Muniroh; Yora Nindita (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
ABSTRACTBackground: Antioxidant is a substance that can catch and neutralize free radicals so that the process of oxidative stress can be stopped and cell damage can be avoided. Kaffir lime peel contains antioxidant compounds that have the potential to be the neuroprotective agent and can protect neurons from free radical-induced damage.Objective: To evaluate the effect of kaffir lime peel extract (Citrus hystrix) on the plasma malondialdehyde (MDA) level of mice induced by Scopolamine (SCM).Method: This research was a true experimental study with a post-test-only controlled group design. Thirty mice were randomly divided into 5 groups consisting of a healthy control (K+), Negative Control (K-), extract 5 mg/20gBW group (P1), 10 mg/20gBW group (P2), 20 mg/20gBW group (P3). SCM was injected intraperitoneally on days 1-7 and kaffir lime peel extract was given orally on days 2-7, the MDA levels testing of mice using TBARS method on day 8. Data analysis used One-Way ANOVA test and continued with Post Hoc LSD test.Results: The mean MDA levels of K+, K-, P1, P2, P3 were 4,212; 4,644; 3,481; 4,555; 4,733 nmol/mL, respectively. MDA levels of P1 were lower than K-, even though there were no statistically significant differences.Conclusion: There was no effect of administration kaffir lime peel extract (Citrus hystrix) on MDA levels in mice with scopolamine-induced dementia.Keywords: Citrus hystrix, malondialdehyde, dementia, mice